Tauhid Perspektif Surat Al-Fatihah (Studi Analisis Konsep Worldvew Islam) - Jarman Arroisi (Universitas Darussalam Gontor, 2019)
The origin of man is monotheism; acknowledging the oneness of God and serving Him. However, in its journey, was most of man forgot his monotheism and disobeyed to serve Him anymore, as a result of their misguidance and destruction. This text intended to know the concept of monotheism in al-Fatihah latter. Through the analytic pattern description, the study found several important points. First, monotheism in al-Fatihah latter was very comprehensive, because it includes monotheism of rububiyah, ulluhiyah and al-asma ’wa al-sifat. Even al-Fatihah latter does not only contain monotheism, but contained the meaning of the entire contents of the Qur'an. Second, any work that started without bismillah will be cut off and has no blessing value. Third, so that one's activities in accordance with his beliefs, a strong will is needed to make monotheism a view of his life. Worldview or one's natural views we are the principle for every human action, including scientific and technological actions. If the concept of monotheism in al-Fatihah letter with all the network of concepts contained in the Qur'an has become a view of life and underlies every activity, monotheism will guide human beings to gain salvation and happiness.